Development of a questionnaire to evaluate the management of gestational diabetes mellitus patients among obstetric nurses - Yongyan Zhu; Yongyan Zhu; Yumin Ren; Jing Ma; Feifei Wan; Feifan Liu; Fangfang Du; Weili Li; Tian Tian; Xiaoqian Liu; Lili Li; Zhumin Jia (Frontiers in Public Health)
BackgroundThe role of obstetric nurses in the management of gestational diabetes mellitus (GDM) is becoming increasingly important, and their management level will directly affect the patient’s health education and even the pregnancy outcome. However, there is a lack of tools to measure the competencies of GDM management among obstetric nurses.MethodsThe questionnaire was developed in two stages: (a) creation of an initial questionnaire based on the definition of competency, literature review, and semi-structured interviews, followed by two rounds of Delphi expert inquiry; (b) evaluation of the questionnaire via piloting study on 30 obstetric nurses and testing of validity and reliability on 239 obstetric nurses.ResultsA questionnaire containing dimensions of professional knowledge, professional skills, professional competence and personal attitude was developed. Correlation analysis revealed statistically significant correlations (p < 0.01) between each item and the total score, although two items had r-values <0.4, indicating weak correlations, so they were removed. The initial Cronbach’s α coefficient of 0.970 indicated that no items needed to be excluded. Five experts evaluated the content validity, yielding an S-CVI/Ave of 0.95 and the I-CVI values range from 0.80 to 1.00, meeting the reference standard. The Cronbach’s α coefficients for the four dimensions ranged from 0.793 to 0.928, while the overall Cronbach’s α coefficient of the questionnaire was 0.970. The retest reliability was 0.907, and the fold-half reliability was 0.950. The results of the reliability tests all met the measurement requirements of the questionnaire and could be used to evaluate the competency of obstetric nurses in the management of GDM patients.ConclusionThis study developed an assessment tool for evaluating the management ability of obstetric nurses for GDM patients, which consists of four dimensions and 35 items. The dimensions and items demonstrate the content of the competence theory, and the questionnaire shows good stability and reliability and validity.Recommendations for practiceIt is recommended that healthcare institutions integrate this questionnaire into training and evaluation programs for obstetric nurses to improve care quality for GDM patients. Regular use will ensure nurses have the knowledge, skills, and attitudes needed to provide optimal care.